Digitalization of Marketing as an Effort to Increase Sales of Agricultural Products : Digitalisasi Pemasaran Sebagai Upaya Meningkatkan Penjualan Produk Pertanian - Muchammad Muchammad; Purwanto Purwanto; Maryono Maryono; Miswan Ansori; Ahmad Fuad Hasyim (CONSEN: Indonesian Journal of Community Services and Engagement, 2023)
Regional development in rural areas is required to play a more intensive role in catching up with other regions in Indonesia and face global competition. Micro, Small, and Medium Enterprises (MSMEs) have an essential role in development in Indonesia. One of the MSMEs that produce many agricultural products is in Tlogo Hamlet, Sutopati Village. The resulting product is processed agriculture, which has been innovated into various types of ready-to-sell food and beverages that are still conventional in their daily marketing. The era of information technology continues to multiply, and people must be aware of technological developments supporting their businesses. This activity aims to empower the community by digitizing the sale of agricultural products. The results of the dedication produced are in the form of increasing the ability of MSME actors to market their products online. MSME actors also have digital marketing online buying and selling accounts on several e-commerce sites.